HUBUNGAN INDEKS MASSA TUBUH (IMT) DENGAN SIKLUS MENSTRUASI PADA REMAJA PUTRI DI SMA N 1 BANGOREJO KABUPATEN BANYUWANGI TAHUN 2022 - diana kusumawati; Herlina Dwi Jayanti; Ukhtul Izzah (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
The menstrual cycle is the duration of time from the first day of menstruation until the next menstruation. One of the factors that can influence the menstrual cycle is body mass index (BMI). This research has a purpose, namely to see the correlation of BMI with the menstrual cycle in adolescent girls at SMA N 1 Bangorejo, Banyuwangi district in 2022.This study used a crosssectionaldesign. Purposive sampling wasused, thetechniquewasused as a sampling technique, thenumberofsamplesusedwas 67 respondents. The instrumentsused were BMI observationsheetsandmenstrualcyclequestionnaires. ThisresearchusestheSpearmanranktest.The results of the study, if most of the young women have a BMI which is in the normal group (43%), and almost all of the young women have menstrual cycles in the normal category (46.3%). The results of the Spearman rank test using the SPSS version 24 application, obtained a p value of 0.000 <0.05 with an r of 0.456, then Ho is rejected, which means that there is a correlation in the direction of BMI and menstrual cycles for adolescent girls in SMA N 1 Bangorejo with moderate strength of relationship.Thisresearchcanbesaidthatadolescentgirlswith normal BMI haveanimpactontheirmenstrualcycle. Therefore, teenagers are advisedtomaintainbodyweightsothatmenstruationisregular.